Plan de Manejo Integral de Residuos Sólidos generados en Plazas y Mercados del Cantón Salcedo, Provincia de Cotopaxi, período 2018. - Escudero Andino, Jimmy Javier (2019)
The development of good environmental practices including the adequate management of solid waste enables the creation of a pleasant environment between workers and society as a whole. For this reason this research project was developed in Salcedo canton, province of Cotopaxi with the main purpose of structuring a plan of integral management of solid waste generated in squares and markets. The research is focused to the environmental problems caused by the management and inadequate management of solid waste, for this, on-site visits were made where the current situation of solid waste management was diagnosed, evidencing that the current ordinances and regulations were not observed. The creation of the waste generation map was also carried out, for doing this was important to calculate per capita production, where the values obtained belong to each trader annually generates around 32.26 kg of which 5.33% belong to organic material while the remaining 94.67% belong to inorganic material. About the design of the solid waste integral management plan (PMIRS), were implemented feasible and applicable techniques, strategies and measures for the adequate management of waste. This plan contains programs for the prevention and mitigation of impacts, citizen participation, training, generation and storage at the source, collection and transport, classification strategies, final disposal, industrial safety and occupational health. The established programs in the PMIRS make it possible to prevent, mitigate and compensate the environmental effects found in squares and markets in Salcedo canton area of study in the present research. The methodology used in the research work included the application of the descriptive, bibliographic and analytical methods; techniques such as: observation, interview and data analysis; as instruments, information matrices were used in which the information and results obtained were synthesized. It’s important to implement the measures and alternatives proposed in the integral solid waste management plan that will help to Salcedo Canton to be one of the cantons with excellent solid waste management.